The test-retest reliability of the H-Reflex and swaymeter in women aged 30–65 years - Rosiered Brownson-Smith; Jack Carr; Kai T. Fox; Samuel T. Orange; Nicola Cresti; John Saxton; John Temesi (PLoS ONE, 2025)
Background The H-reflex can objectively assess sensorimotor integration relevant to proprioception and postural control. Chemotherapy-induced peripheral neuropathy (CIPN) is a common and potentially dose-limiting side effect among breast cancer patients undergoing taxane-based treatments, leading to proprioception loss and balance issues, and an increased risk of falling. This study evaluated the between-day test-retest reliability of neurophysiological measures and postural sway, measured via swaymeter in a demographically similar population to those affected by breast cancer. Methods 25 women aged 30–65 years were assessed on two occasions, approximately two weeks apart. The study measured between-day test-retest reliability of the soleus H-reflex and M-wave and postural sway, measured by the swaymeter. Results The soleus maximum H-reflex amplitude (Hmax) and maximum M-wave amplitude (Mmax) exhibited good to excellent (ICC = 0.92, 95% CI: 0.82–0.96) and moderate to excellent (ICC = 0.81, 95% CI: 0.62–0.91) between-day reliability, respectively. The Hmax/Mmax showed poor to good between-day reliability (ICC = 0.63, 95% CI: 0.31–0.82), and H-reflex latency demonstrated moderate to excellent between-day reliability (ICC = 0.83, 95% CI: 0.65–0.92). The between-day test-retest reliability of anteroposterior (AP) displacement and total sway across the two testing sessions was poor to moderate (ICC = 0.37, 95% CI: −0.03–0.66 and ICC = 0.42, 95% CI: 0.04–0.70, respectively). Conclusions H-reflex and M-wave measures are reliable for between-day assessments. However, sway measures via swaymeter were less reliable, indicating a need for more robust tools to evaluate balance.